Pengembangan Usaha Mikro Kecil dan Menengah (UMKM) produk Chucok (churros coklat) sebagai Solusi Pengentasan Kemiskinan Pada Musim Paceklik di Desa lubuk Cuik, Kab. Batu Bara - Adlini, Miza Nina; Oktariani, Cindy; Siregar, Mahnida Zahra; Lubis, Suci Fitria (Journal Of Human And Education (JAHE), 2024)
This activity aims to develop Micro, Small and Medium Enterprises (MSMEs) with Chucok products (chocolate churros) as a solution to poverty alleviation in Lubuk Cuik Village, Batu Bara Regency, especially during the lean season. In difficult economic conditions during the lean season, many village communities experienced a decline in income. Through the development of MSMEs based on processed food products, namely Chucok (chocolate churros), it is hoped that this can become an alternative source of income for the community. The activity implementation method used is a seminar by providing an explanation of the material and how to make churros products. The results of the activity show that Chucok (chocolate churros) MSMEs have the potential to increase village residents' income, create new jobs, and reduce poverty rates, especially during difficult times such as the lean season. Support from the government and other stakeholders is also needed for the sustainability of this business.